Answer:
15
Step-by-step explanation:
5 divided by 1/3 is the same as if you flip the denominator meaning 5 x 3 which is 15
This may not be very pretty.
(2x + 5) * (2x + 5) expanded is (use foil)
F = 4x^2
O = 2x * 5 = 10x
I = 2x + 5 = 10x
L = 25
Total = 4x^2 + 20x + 25
(x + 3)(x + 3) = x^2 + 6x + 9 by the same method
(2x + 7)(2x + 7) = 4x^2 + 28x + 49 Same method.
4x^2 + 20x + 25 + x^2 + 6x + 9 = 4x^2 + 28x + 49
5x^2 + 26x + 34 = 4x^2 + 28x + 49 Collect everything on the left.
x^2 - 2x - 15 = 0
(x - 5)(x + 3) = 0
x + 3 will have no meaning.
x - 5 = 0
x = 5
2x + 5 = 2*5 + 5 = 15
x + 3 = 5 + 3 = 8
2x+ 7 = 2*5 +7 = 17
Check
15^2 + 8^2 = 17^2
225 + 64 = ? 289
289 = 289
a = 15 <<<<< answer
b = 8 <<<<< answer
c = 17 <<<<< answer
Answer:
y=-1
Step-by-step explanation:
Answer:
f(g(x)) = 15x + 2
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Distributive Property
<u>Algebra I</u>
- Functions
- Function Notation
- Composite Functions
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify</em>
f(x) = 5x + 7
g(x) = 3x - 1
<u>Step 2: Find</u>
- Substitute in functions: f(g(x)) = 5(3x - 1) + 7
- [Distributive Property] Distribute 5: f(g(x)) = 15x - 5 + 7
- [Addition] Combine like terms: f(g(x)) = 15x + 2